Pengaruh Ukuran Perusahaan, Leverage, Profitabilitas, Industri, Umur Perusahaan, Masa Jabatan Perusahaan Audit, dan Ukuran Perusahaan Audit terhadap Corporate Social Responsibility - Anita Anita; Jeny Jeny (Universitas Internasional Batam, 2021)
Corporate Social Responsibility (CSR) is a general corporate movement that is responsible to various stakeholders who benefit society. The purpose of this study is first to determine the relationship between company characteristics, namely company size, leverage, profitability, industry and company age with the disclosure of social responsibility of companies listed on the Indonesia Stock Exchange (IDX); second, to determine the relationship between the level of corporate social responsibility disclosure with several audit variables such as tenure of the audit firm and the size of the audit firm. The results showed that there was a significant positive relationship between company size, leverage, industry and audit firm size on CSR.